2018
DOI: 10.1038/s41418-018-0078-7
|View full text |Cite
|
Sign up to set email alerts
|

DeSUMOylation switches Kaiso from activator to repressor upon hyperosmotic stress

Abstract: Kaiso is a member of the BTB/POZ zinc finger family, which is involved in cancer progression, cell cycle control, apoptosis, and WNT signaling. Depending on promoter context, it may function as either a transcriptional repressor or activator. Previous studies found that Kaiso might be SUMOylated due to heat shock, but the biological significance of Kaiso SUMOylation is unclear. Here, we find that K42 is the only amino acid within Kaiso that is modified with SUMO. Kaiso is monoSUMOylated at lysine 42 in cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…Interestingly, ZBTB33 is also able to function as a methyl-dependent activator [43]. A more recent work by Zhenilo et al suggests that SUMOylation in ZBTB33 BTB/POZ protein-protein interaction domain may switch ZBTB33 from a gene repressor to an activator [44].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, ZBTB33 is also able to function as a methyl-dependent activator [43]. A more recent work by Zhenilo et al suggests that SUMOylation in ZBTB33 BTB/POZ protein-protein interaction domain may switch ZBTB33 from a gene repressor to an activator [44].…”
Section: Discussionmentioning
confidence: 99%
“…Kaiso functions both as a transcription repressor, and as an activator, depending on the tissue microenvironment, but its activity is also regulated by post-translational modifications (e.g. phosphorylation, SUMOylation) [26, 27]. While our study was the first to implicate Kaiso in intestinal inflammation, the incipient stages of this process have not yet been elucidated.…”
Section: Introductionmentioning
confidence: 98%
“…A recent study by Zhenilo et al investigated the effect of post translational modifications on Kaiso’s transcriptional activity [26] and found that covalent linkage of small ubiquitin-like modifier (SUMO) polypeptides functioned as a molecular switch to regulate Kaiso’s function as an activator or repressor [26]. When SUMOylated, Kaiso acted as an activator but when deSUMOylated, Kaiso acted as a repressor (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…When SUMOylated, Kaiso acted as an activator but when deSUMOylated, Kaiso acted as a repressor (Figure 1). Using HEK293 cells, the authors demonstrated that Kaiso is SUMOylated under normal conditions at lysine 93 (K93); however, under hyperosmotic stress, Kaiso was found to be deSUMOylated [26]. This was the first study to elucidate a role for post-translational modifications on Kaiso function and indicates that further work is needed to examine other mechanisms (e.g.…”
Section: Introductionmentioning
confidence: 99%